The Ketogenic and modified Atkins diets : treatments for epilepsy and other disorders - Mackenzie C. Cervenka; Sarah Doerrer; Bobbie J. Henry; Eric H. Kossoff; Zahava Turner (Demos Health, 2016)
Now in its sixth edition, The Ketogenic and Modified Atkins Diets is the established, authoritative book on these groundbreaking epilepsy treatments. Written for parents, patients, dieticians, and neurologists, this book is an invaluable resource for anyone considering or starting a ketogenic diet for epilepsy or another neurologic disorder. Written by doctors, dieticians, and a pediatric nurse practitioner from the Johns Hopkins Hospital's Ketogenic Diet Center, along with several other experts in the field, this book's patient-centered content contains answers to almost any question related to the ketogenic and modified Atkins diets, for children and adults. Chapters cover implementation, recipes, fine-tuning the diets, connecting with support groups, the latest research on the effectiveness of the diets, and much more. The sixth edition has been thoroughly revised and updated to reflect current advances and applications. Two entirely new sections are devoted to the use of ketogenic diets for epilepsy in adults, and diets that can help alleviate the symptoms of other conditions such as cancer, dementia, autism, and migraines. Coverage of the modified Atkins diet is significantly expanded to reflect the growing popularity of this less restrictive diet. Neatly organized into nine sections, this essential book will help you: Understand how the ketogenic and modified Atkins diets work Prepare for the lifestyle changes involved in following these diets Start, maintain, fine-tune, and eventually stop the diet Develop tasty and healthy ketogenic meals Connect with local and worldwide resources for epilepsy-related issues Understand the latest research about the diet for use in kids and adults Navigate the "non-keto" world (schools, family, friends) with confidence "It will end up being the most well-read book you own and every keto home should have one. My copy went everywhere with me when Matthew was on the diet and I can't recommend it highly enough."?Emma Williams, CEO/Founder, Matthew's Friends Charity, Dietary Treatments for Epilepsy, GLOBAL; Director, Matthew's Friends Clinics Ltd. for Ketogenic Dietary Therapies "If we had had the information in this book fifteen months earlier, a vast majority of Charlie's $100,000 of medical, surgical, and drug treatment would not have been necessary, a vast majority of Charlie's seizures would not have occurred."?From the Foreword by Jim Abrahams, Director, The Charlie Foundation to Help Cure Pediatric Epilepsy